Ocular surface squamous neoplasia: angiographic characteristics and response to subconjunctival/perilesional 5-fluorouracil injections - Sun Y; Hua R (Dove Medical Press, 2019)
Yuzhao Sun, Rui HuaDepartment of Ophthalmology, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning 110001, People’s Republic of ChinaIntroduction: To investigate the angiographic characteristics of ocular surface squamous neoplasia (OSSN) and to evaluate the efficacy of subconjunctival/perilesional 5-fluorouracil injections in OSSN cases.Materials and methods: Six eyes of six patients with primary OSSN, received perilesional, subconjunctival, 25-mg/mL 5-fluorouracil injections at certain intervals. Anterior segment digital photography images, anterior segment optical coherence tomography (AS-OCT), and conjunctival indocyanine green angiography (ICGA) were obtained simultaneously with fluorescein angiography.Results: The mean best-corrected vision acuity significantly improved after treatment. At baseline, the median of the largest thickness of OSSN was 905.0 (interquartile range: 492.0–1592.5) μm based on AS-OCT data. There was an abrupt transition between normal and abnormal epithelium, a thickened hyper-reflective epithelium, and a sharp plane of cleavage between the lesion and underlying tissue, all indicative of OSSN. The angiographic characteristics of OSSN included focal or seafan-shaped intratumoral and conjunctival feeding vessels visible via ICGA, and abnormal vascular leakage visible with fluorescein angiography. The median time to tumor regression after treatment was 35.0 (interquartile range: 32.0–45.5) days in five eyes without recurrence, and OSSN in one eye regressed partially 40 days after treatment.Conclusion: This is the first report of the angiographic characteristics of OSSN and its response to subconjunctival/perilesional 5-fluorouracil injections by simultaneous conjunctival angiography and AS-OCT. The improved subconjunctival/perilesional 5-fluorouracil injection was an effective therapy for OSSN in both best-corrected vision acuity gain and anatomic outcomes.Keywords: ocular surface squamous neoplasia, subconjunctival 5-flourouracil injection, conjunctival angiography, anterior segment optical coherence tomography